THU0549 Decoy Receptor 3 Regulates the Expression of Tryptophan Hydroxylase TPH1 in Rheumatoid Synovial Fibroblasts. (10th June 2014) - Maeda, T.; Miura, Y.; Fukuda, K.; Hayashi, S.; Kurosaka, M.
Abstract : Background: Tryptophan hydroxylase (TPH) which catalyzes the hydroxylation of L-tryptophan is the rate-limiting enzyme involved in the synthesis of serotonin. TPH has two isoforms; TPH1 expresses in peripheral and central nerve system (CNS) tissues expressing serotonin, such as skin, intestine, and pineal gland, while TPH2 expresses exclusively and dominantly in CNS. Recently several studies suggested that serotonergic systems play an important role in modulating inflammatory pain and bone remodeling [1]. We previously reported that decoy receptor 3 (DcR3), a member of TNF receptor superfamily, overexpressed in rheumatoid synovial fibroblasts (RA-FLS) stimulated with TNFα inhibits Fas-induced apoptosis [2]. We recently reported that DcR3 induced VLA-4 expression in THP-1 macrophages to inhibit cycloheximide-induced apoptosis [3], and that DcR3 inhibited cell proliferation induced by TNFα or IL-1β via TL1A expressed on RA-FLS [4]. We also reported that the concentration of DcR3 in sera and joint fluids of patients with RA was significantly higher than with osteoarthritis (OA) [5]. Further, by using comprehensive genetic analysis using microarrays, we newly identified TPH1 as one of the genes of which expression in RA-FLS was suppressed by DcR3 [6]. Objectives: In this study, we investigated the expression of TPH1 in RA and OA-FLS stimulated with DcR3 and inflammatory cytokines to elucidate the involvement of TPH1 and DcR3 in the pathogenesis of RA. Methods: Real-time polymerase chain reaction (real-time PCR). Primary cultured RA or OA-FLS were incubated with 1.0 μg/ml recombinant human DcR3-Fc protein or 1.0 μg/ml control IgG1 for 12 hours, or 1.0 ng/ml recombinant human TNFα or 1.0 ng/ml IL-1β for 24 hours, then the relative expression levels of TPH1 mRNA were quantified by real-time PCR. Immunohistochemistry. Serotonin expressed in RA-FLS was detected by immunohistochemistry. Results: TPH1 mRNA was expressed in both RA and OA-FLS. TPH1 mRNA expression was decreased significantly by DcR3 in RA-FLS, but not in OA-FLS. Meanwhile, TPH1 mRNA expression was significantly decreased by TNFα or IL-1β both in RA and OA-FLS. Serotonin expression in RA-FLS was confirmed by immunohistochemistry. Conclusions: In this study, we first revealed that the expression of TPH1 in FLS was down-regulated by the inflammatory cytokines and that TPH1 in RA-FLS was suppressed by DcR3 in a disease-specific fashion. Serotonin synthetized by TPH1 is suggested to have pleiotropic effects other than physiological functions. Serotonergic pathways especially play an important role in modulating inflammatory pain, compared with mechanistic pain. Further, serotonin decreases osteoblast proliferation and bone formation and increases the total number of differentiated human osteoclasts as well as osteoclast activity. Therefore, TPH1 expression in RA-FLS regulated by DcR3 in a disease specific manner may affect serotonin expression to be involved in the pathogenesis of RA, such as modulating inflammatory pain and bone remodeling. Both DcR3 and TPH1 could be a possible therapeutic target of RA. References: Patricia D. et.al., J Cell biol, 191, 7-13, 2010 Hayashi S. et al., Arthritis and Rheum, 56, 1067-1074, 2007 Tateishi K. et al., Biochem Biophys Res Commun, 389, 593-598, 2009 Takahashi M. et al., Int J Mol Med, 28, 423-427, 2011 Hayashi S. et al., Mod Rheumatol, 20, 63-68, 2009 Fukuda K. et al., Int J Mol Med, 32, 910-916, 2013 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4859